Synthesis and in vitro Evaluation of New Hydrazones as Pyrrole Derivatives with Anti-tubercular Activity - Bijev, Atanas (Arzneimittelforschung, 2009)
Fourteen new hydrazones representing derivatives of pyrrole were synthesized by condensation of six carbohydrazides with ten carbonyl compounds. The new products were evaluated as potential tuberculostatics by means of two levels of high-throughput screening. The preliminary screening against Mycobacterium tuberculosis H37Rv (ATCC 27294) at 6.25 µg/mL in 12B medium using the Microplate Alamar Blue Assay measured the inhibitory activity within the total series in the range of 98–0%. Compound 3-i (N 4-[l-(4-acetyl-3,5-dimethyl-lH-2-pyrrolyl)-methylidene]-4-pyridinecarbohydrazide) was identified as the compound showing the highest inhibition (98%) and was subjected to level 2 screening, whereat the resulting data (IC50 < 0.2 and IC90 = 22.581) identified 3-i as a prospective candidate for further and more detailed evaluations.The inhibitory activity within the series was found to drop with the increase of the relevant dipole moments and all the inactive compounds distinguished themselves with a higher molecular polarity.
Keywords: Carbohydrazides; Pyrrole derivatives, hydrazones, synthesis, tuberculostatic activity; Tuberculostatics